El registro sedimentario Pleistoceno tardío-Holoceno de la Salina de Ambargasta (Argentina central): una aproximación paleolimnológica - Zanor, Gabriela Ana (2013)
Salina de Ambargasta is a playa system located at the middle latitude of Argentina (29°S; 64°W). Two sedimentary cores retrieved at the eastern border (AB-1) and the central area of the salina (AB-2) were studied using a multi-proxy approach, an actualistic sedimentary model and radiocarbon dates allowed reconstructing the paleohydrological history of the Salina de Ambargasta since the late Pleistocene. The paleoenvironmental reconstruction for the last ca. 45,000 years to the present suggests six main environmental stages: 1) between 44,700 and 39,600 cal. year BP, a dry period is represented by the development of a capillary mudflat; 2) between ca. 39,600 and 26,700 cal. year BP a more humid period is recorded by lacustrine facies with carbonate and sulfate precipitation; 3) between ca. 26,700 and 23,600 cal. year BP occurs the most humid phase in Ambargasta, characterized by the sedimentation in an ephemeral sulfate lake, relatively deep, enriched with microbial mats and fringed by mudflats; 4) between 23,600 and 18,500 cal. year BP, a change to drier conditions with humid pulses is evidenced by the development of saline mudflats alternating with ephemeral lakes and associated with mudflats in the supralittoral areas; 5) between 18,500 and 8,600 cal. year BP a drier period is identified by the dominance of capillary and saline mudflats, and 6) since 8,600 cal. year BP to the present the most negative hydrological balance is recorded in the saline system, represented by an expansion of capillary mudflats The control of the hydrological balance in the Salina de Ambargasta is mostly associated with the variation of the South America Monsoon–like System. Thus, the record presented here allows us to provide new clues in order to decipher former fluctuations of this important driver of the climatic system of South America since the late Pleistocene.